1996
DOI: 10.1037/h0080165
|View full text |Cite
|
Sign up to set email alerts
|

War-induced psychic trauma: An 18-year follow-up of Israeli veterans.

Abstract: Eighteen years after their participation in the Yom Kippur War, the psychiatric status of two groups of Israeli veterans--112 combat stress reaction casualties and 189 comparable controls--was assessed. Casualties had higher rates and greater intensity of posttraumatic stress disorder than did controls, both initially and at 18-year follow-up. Similarly, intrusion and avoidance tendencies and psychiatric symptomatology were evidenced more often by combat stress reaction casualties than by controls. Clinical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A large number of PTSD follow-up studies of warrelated trauma in adults are uniform in demonstrating the chronic nature of this syndrome: prisoners of war (Tennant et al, 1997); concentration camp survivors (Drozdek, 1997); Vietnam veterans (Grayson et al, 1996); Operation Desert Storm veterans (Southwick et al, 1995); World War II veterans (Leeet al, 1995); and Yom Kippur War veterans (Solomon and Kleinhauz, 1996). Amir et al (1996) showed that battle-derived PTSD appeared to be the most severe form of trauma when its victims were compared with victims of terrorism, traffic accidents, and work-related accidents in adults.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of PTSD follow-up studies of warrelated trauma in adults are uniform in demonstrating the chronic nature of this syndrome: prisoners of war (Tennant et al, 1997); concentration camp survivors (Drozdek, 1997); Vietnam veterans (Grayson et al, 1996); Operation Desert Storm veterans (Southwick et al, 1995); World War II veterans (Leeet al, 1995); and Yom Kippur War veterans (Solomon and Kleinhauz, 1996). Amir et al (1996) showed that battle-derived PTSD appeared to be the most severe form of trauma when its victims were compared with victims of terrorism, traffic accidents, and work-related accidents in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen years after the Yom Kippur War, CSR veterans were found have lower PTSD recovery rates than comparable control veterans; 37% of the veterans with antecedent CSR reported to have suffered from PTSD, compared to 23% of the comparable veterans without a diagnosis of CSR (Solomon & Kleinhauz, 1996). Furthermore, these veterans with CSR also had higher rates of physical symptoms, adverse health practices (Neria, & Koenen, 2003) and general psychiatric symptoms (Neriaet al, 2000).…”
Section: Csr Studiesmentioning
confidence: 99%
“…It has been argued that CSR is a rational reaction to an irrational situation (1) where once the distressed soldier is removed from the stressors of war, they will regain their equilibrium and functionality (10,12). To the best of my knowledge, the majority of largescale prospective studies of CSR have been conducted in Israel involving combatants from the 1973 Yom Kippur War [e.g., (13)] and the 1982 Lebanon War [e.g., (2,8)]. In particular, in the Yom Kippur study, CSR casualties were identified as a high-risk group for PTSD and other psychiatric and somatic co-morbidities (13).…”
Section: Is Csr Short Lived and Transient?mentioning
confidence: 99%
“…To the best of my knowledge, the majority of largescale prospective studies of CSR have been conducted in Israel involving combatants from the 1973 Yom Kippur War [e.g., (13)] and the 1982 Lebanon War [e.g., (2,8)]. In particular, in the Yom Kippur study, CSR casualties were identified as a high-risk group for PTSD and other psychiatric and somatic co-morbidities (13).…”
Section: Is Csr Short Lived and Transient?mentioning
confidence: 99%